PENGARUH KEPUASAN, KEPERCAYAAN, SERTA VARIETY SEEKING TERHADAP PERILAKU BRAND SWITCHING - Dana, I Putu Arya; Warmika, I Gde Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Brand Switching is a phenomenon that is usually experienced by consumers in choosing a product. It is very important to be noticed by the company because brand switching is closely related to customer satisfaction. The purpose of this study is to explain the effect of satisfaction, trust, and variety seeking on brand switching behavior. This research was conducted in several branches of Kopi Kulo in Denpasar City. Samples were taken as many as 100 respondents through purposive sampling method and distributed using a google form questionnaire with adjusted criteria. Measured by 13 indicators and using a Likert scale. The data analysis technique used is multiple linear regression test. The results of this study indicate that all hypotheses are accepted. Satisfaction has a positive and significant effect on brand switching. Trust has a positive and significant effect on brand switching. Variety seeking has a positive and significant effect on brand switching. This research are expected to be considered and input for management at Kopi Kulo in Denpasar City in marketing their products by considering satisfaction, trust, variety seeking and brand switching behavior